Anti-Communism in Australian Immigration Policies 1947–54: The Case of Russian/Soviet Displaced Persons from Europe and White Russians from China. Issue 1 (2nd January 2019) - Fitzpatrick, Sheila; Greenwood, Justine
Abstract : This article assesses the role of anti-Communism in Australia's postwar immigration policy in the years before the Petrov affair, with particular reference to the entry of Russians and Russian-speaking Jews from Europe and China. Our discussion focuses on the Department of Immigration under Arthur Calwell and his successor, Harold Holt, and the security agency, ASIO. We conclude that policy in this sphere was essentially bipartisan, and that anti-Communism was an important but not overwhelming motivation, stronger than the desire to prevent entry of Nazis and war criminals but probably less salient in practice than concern to minimise the entry of Jews.